Malignant renal tumours seen in the University of Port Harcourt Teaching Hospital, Port Harcourt, Nigeria - Obiorah, Christopher C; Ofuru, Vitalis (African Journal of Nephrology, 2017)
Introduction: Malignant renal tumours (MRTs) pose significant morbidity and mortality. In adults, renal cell carcinoma (RCC) constitutes about 90% of these tumours whereas in children, the majority are nephroblastomas. Males are generally more affected than females. Nuclear grade, tumour stage, size and histopathological subtype are prognostic factors. In our environment, patients with MRTs commonly present late. Methods: Clinical and demographic details of patients who had malignant tumours diagnosed on renal biopsy tissue between 2002 and 2013 at the University of Port Harcourt Teaching Hospital, Port Harcourt, Nigeria, were extracted from pathology request forms. Slides were retrieved from the archives and reviewed. The tumours were classified according to WHO and ISUP criteria. Results: Kidney biopsies constituted 0.8% of the biopsy specimens processed within the period; 60% of these were malignant lesions. Half (51%) of the patients with MRTs were males and 81% were children (the majority aged 0–4 years). Among children, the incidence decreased steadily with age. Seventy-three percent were nephroblastomas, exclusively occurring in children. Renal cell carcinoma constituted 19.4%, with papillary carcinoma being the commonest subtype, whereas non-Hodgkin’s lymphoma and rhabdomyosarcoma constituted 6% and 1.5%, respectively. The mean gross weight of the tumour masses was 1.3 kg and the average duration of symptoms prior to presentation was 18.3 months. The majority presented with abdominal masses. Conclusion: Although the renal biopsy rate is generally low in our environment, we found that the most common renal malignancy was nephroblastoma in children. In adults, renal cell carcinoma, mainly of the papillary type, was predominant. Most cases present late.